Subendothelial infiltration of neutrophil granulocytes and liberation of matrix-destabilizing enzymes in an experimental model of human neo-intima - Dorweiler, Bernhard; Torzewski, Michael; Dahm, Manfred; Kirkpatrick, Charles James; Lackner, Karl J.; Vahl, Christian-Friedrich (Thrombosis and Haemostasis, 2008)
It was the objective of this study to examine the role of human neutrophil granulocytes (PMN) in an in-vitro model of human neo-intima developed for the study of atherosclerosis. Human granulocytes were subjected to a co-culture model of human endothelial and smooth muscle cells. Subendothelial lipid accumulation was achieved by addition of native LDL to the culture medium. Tissue samples were analyzed by immunohistochemistry and scanning/transmission electron microscopy, and culture supernatants were examined for the presence of interleukin- 8 (IL-8), MCP-1, GRO-α, elastase and matrixmetalloproteinase-8 (MMP-8). Following addition of 2 mg/ml LDL, adherence, transmigration and infiltration depth of PMN was increased significantly when compared to controls. LDL challenging was paralleled by a time- and dose-dependent secretion of IL-8 from intimal smooth muscle cells. PMN infiltration was mediated by the IL-8-signalling pathway and accompanied by release of elastase and MMP-8 into the supernatant and induction of endothelial cell apoptosis. In conclusion, LDL-induced secretion of IL-8 by intimal smooth muscle cells provides a potential mechanism of PMN-recruitment into culprit lesions. The concomitant release of potent matrix-degrading enzymes and the induction of EC apoptosis may have implications for plaque destabilization and cardiovascular events.
Keywords: Atherosclerosis; endothelium; proteases; leukocyte recruitment; apoptosis